Voluntary Disclosure, Credibility, and Triggering Factors of Voluntary Disclosure: An Overview of Beneficial Study Reviews - Dielanova Wynni Yuanita; Christine Novita Dewi (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The economic development as a trigger of mandatory disclosure has no longer provided information needed by stakeholder, especially the primary users including investors and creditors. The high information demand from stakeholder urges company to reveal their information through voluntary disclosure. An inquiry to voluntary disclosure has been an interesting discussion and extensively studied in Indonesia as well as the rest of the world. It is obvious because the subject solidates relationship between company with investors, attracts potential investors, and reduces capital risk. The ultimate factor of voluntary disclosure (either in Indonesia or worldwide) is size of company. Those companies which reveal voluntary disclosure in the form of information content, wheter good news or bad news, might obtain feedback from the market in form of price increase or price decrease in stock prices.